Analysis of characteristics, frequency of eating fruit and vegetables in diabetes and non diabetes patients - Putra Apriadi Siregar (Darussalam Nutrition Journal, 2021)
Background:Fruits and vegetables are foods that are recommended for consumption by people to prevent diabetes mellitus because they are low in sugar and have fibre that can bind sugar. The consumption pattern of fruits and vegetables consumed by DM patients and non-DM sufferers is an important thing to know. Objective: to determine the characteristics and frequency of eating fruits and vegetables in diabetics and non-diabetics. Method: The study used a cross-sectional design which was conducted in Belawan I Village, Deli Serdang Regency from August to December 2019. The number of samples in this study was 90 people who were selected by purposive sampling. This research is a research by conducting direct interviews with the community but using the Riskesdas 2018 questionnair. Result: This study indicates that DM sufferers tend to consume 2-3 servings of vegetables per day, but many DM sufferers still do not consume fruit every day. People who do not have diabetes tend to consume 2-3 servings of vegetables per day and consume 2-3 servings of fruit per day. People who do not eat fruit are at 8,094 times the risk of suffering from diabetes mellitus compared to respondents who eat fruit (2-3 servings/day). Fruit consumption is an important factor in reducing the risk of diabetes mellitus.